2016
DOI: 10.1007/7854_2016_37
|View full text |Cite
|
Sign up to set email alerts
|

Immune-to-Brain Communication Pathways in Inflammation-Associated Sickness and Depression

Abstract: A growing body of evidence now highlights a key role for inflammation in mediating sickness behaviors and depression. Systemic inflammatory diseases such as rheumatoid arthritis, inflammatory bowel disease, and chronic liver disease have high comorbidity with depression. How the periphery communicates with the brain to mediate changes in neurotransmission and thereby behavior is not completely understood. Traditional routes of communication between the periphery and the brain involve neural and humoral pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
129
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 108 publications
4
129
0
10
Order By: Relevance
“…Although the origin of vasomotor autonomic dysfunction in PBC remains unclear, there is evidence to suggest a central component, including a link between autonomic dysfunction and cognitive dysfunction . Interestingly, elevated circulating levels of the proinflammatory cytokine TNFα have been implicated in the development of sickness behaviours, including fatigue, in animal models of liver disease . Similar observations have been made in patients with chronic nonhepatic inflammatory diseases, including rheumatoid arthritis and inflammatory bowel disease .…”
Section: Fatigue In Liver Diseasementioning
confidence: 80%
See 2 more Smart Citations
“…Although the origin of vasomotor autonomic dysfunction in PBC remains unclear, there is evidence to suggest a central component, including a link between autonomic dysfunction and cognitive dysfunction . Interestingly, elevated circulating levels of the proinflammatory cytokine TNFα have been implicated in the development of sickness behaviours, including fatigue, in animal models of liver disease . Similar observations have been made in patients with chronic nonhepatic inflammatory diseases, including rheumatoid arthritis and inflammatory bowel disease .…”
Section: Fatigue In Liver Diseasementioning
confidence: 80%
“…However, the gut microbiome is also an important regulator of brain function, and changes in the gut microbiome are capable of affecting mood, cognition and behaviour . Moreover, it is clear that changes in gut microbiota can modulate brain function in the setting of liver disease . Two main peripheral communication pathways have been implicated in gut microbiota—brain interactions; namely, the neural and humoral pathways (Figure ) .…”
Section: Fatigue In Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of cerebral blood flow and perfusion in these patients may result from two potential mechanisms: (1) disrupted efferent sympathetic nervous control of arterial blood pressure and/or (2) direct damage or injury to the vascular endothelial cells, both of which may cause dysfunctional vasomotor activity. Previously, we have shown that following bile duct ligation in mice, liver inflammation induces an immunological assault on the endothelial cells of cerebral blood vessels, providing evidence of the latter as a potential driver of altered cerebral vasomotor regulation of cerebral blood flow found in patients with chronic liver inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…Although prevalence estimates vary geographically, a recent US study reports a PBC prevalence of 4.3 per 100,000 in women and 1.1 per 100,000 in men, and similar findings have been reported in Canada . PBC is commonly associated with a number of behavioral symptoms including fatigue, itch, altered mood, and cognitive changes, indicating that PBC can alter brain function . However, the mechanism whereby PBC can impact brain function remains unknown.…”
mentioning
confidence: 78%